Conceptualising a Grid Resilience Framework for Renewable Energy Integration - Mashele, L.M.M.; Thopil, G.A.; Oerlemans, L. (The South African Journal of Industrial Engineering, 2025)
Given their variability and intermittency, renewable energy sources need a robust and resilient grid framework. With increasing renewable integration in South Africa, grid instability and infrastructure vulnerability become significant problems. This paper explores the complexities of the South African energy system while balancing operator requirements in the Southern African region’s unique context. Through a multidisciplinary approach, it develops a framework that includes various levels of renewable penetration. It proposes technical and operational solutions for ecological grid resilience. The framework draws on contemporary research, case studies, and energy system modelling, emphasising advanced grid infrastructure, smart grid technologies, flexible operations, real-time monitoring, and predictive analytics. It provides practical insights for engineers, policymakers, and industry stakeholders to develop resilient energy systems, ensuring grid resilience and energy security in Southern Africa.